The Potential of Incorporating a Pharmacist-Only Medicine Category in Poland - Tomasz Zaprutko; Józefina Sprawka; Barbara Maciuszek-Bartkowska; Piotr Ratajczak; Dorota Kopciuch; Anna Paczkowska; Krzysztof Kus (MDPI AG, 2024)
Pharmacists play an important role, being increasingly focused on patient care and pharmaceutical services. This trend is also noticeable in Poland. Thus, we aimed to study the opinions of Polish pharmacists to determine the potential for introducing a new category of pharmacist-only medicines (POMs). This study was conducted during the COVID-19 pandemic. Hence, the survey (anonymous questionnaire consisting of 10 questions addressed to pharmacists) was only available in electronic form. A total of 500 correctly completed surveys were collected and subjected to further analysis. The vast majority of pharmacists (91.8%) revealed a willingness to expand their professional rights and 88% stated that the POMs implementation would be important. As a substance that should function as a POM instead of an OTC medicine, respondents most often indicated ketoprofen, sildenafil, and mometasone, accounting for 26.2%, 24.8%, and 24.4% of responses, respectively. In terms of funding pharmaceutical services, 54.2% of respondents indicated that costs should be covered partially by the patient and the payer. There is a clear need for the incorporation of the POM category in Poland. Polish pharmacists are anticipating the development of pharmaceutical services which should be partly covered by patients and payers.